Construction of dual-carbon-confined metal sulfide nanocrystals via bio-mimetic reactors enabling superior Fenton-like catalysis. Issue 40 (5th October 2021) - Xu, Tao; Long, Yanping; He, Chao; Song, Xin; Zhao, Weifeng; Zhao, Changsheng
Abstract : Dual-carbon-confined metal sulfide nanocrystals fabricated via a seaweed-mimetic reactor demonstrated the highest efficiency for peroxymonosulfate activation. Abstract : Peroxymonosulfate (PMS) based Fenton-like reactions are widely proposed for the degradation of refractory pollutants. However, the contradiction between achieving delicate architecture of efficient Fenton-like catalysts and the inevitable high operation cost remains to be reconciled. Herein, inspired by the cascaded bio-mineralization mechanism of seaweed, we propose a scalable and all-encompassing seaweed-mimetic reactor (SMR) to construct dual-carbon-confined metal sulfide (Co9 S8 ) nanocrystals. Benefiting from the Co9 S8 core with the dual-carbon-confined structure, the as-prepared catalysts show splendid degradation efficiency towards organic pollutants (100% in 14 min for rhodamine B) via activation of PMS. The integration of the catalysts in a continuous-flow catalytic reaction system achieves a 90% degradation ratio of 28 L rhodamine B-containing wastewater (20 mg L −1 ) using only 1 g catalyst. In addition, feasibility and sustainability are guaranteed with ultra-low cost (only $0.065 g −1 ), convenient preparation procedures, and a balanced environmental burden. It is suggested that this efficient, sustainable, and cost-effective SMR-assisted strategy not only provides promising Fenton-like catalysts for practical wastewater remediation, but also takes a step toward the production of advanced metal sulfide/carbon heterostructures for diverse catalytic and energy applications.